(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The morphology of the glandular apparatus in the wall of the ampulla of the Vater’s papilla of rabbits, ground squirrels, dogs and cats were studied. It was found that not all laboratory animals have the same amount of glands in the wall of the ampulla of the Vater’s papilla. The highest concentration of glands in the proper plate of the ampulla was found in rabbits and ground squirrels, and an insignificant amount in dogs and cats.